2006
DOI: 10.1227/01.neu.0000245623.70344.f7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Ruptured Intracranial Aneurysms

Abstract: Discrepancies with the results of other published studies, procedural limitations in study design, and lack of some data endpoints and subgroup analysis raise concerns regarding extracting generalizations from the conclusions of ISAT. We think that the creation of a national registry would further the study of treatment of ruptured intracranial aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Besides, some authors suggest that small aneurysms are associated with more extensive SAH. [45] Taylor et al [46] reported that aneurysms <5 mm tend to a more significant association with a higher score on the Fisher scale, although there was no difference in the incidence of vasospasm or overall outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, some authors suggest that small aneurysms are associated with more extensive SAH. [45] Taylor et al [46] reported that aneurysms <5 mm tend to a more significant association with a higher score on the Fisher scale, although there was no difference in the incidence of vasospasm or overall outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular treatment is one of the most important treatments along with open craniotomy for cerebrovascular surgery 3)7)9). For successful treatment, the proper selection of devices is important as well as the operator's experience.…”
Section: Introductionmentioning
confidence: 99%
“…A neurysmal subarachnoid hemorrhage (aSAH) affects more than 500 000 individuals annually and is associated with significant morbidity and mortality. [1][2][3][4] Historically, aSAH was primarily treated with microsurgical clipping. After the advent of modern endovascular techniques, many centers shifted to an endovascular approach as the primary treatment 1,5 because it is minimally invasive and has proven efficiency and efficacy in randomized controlled trials.…”
mentioning
confidence: 99%